Digitalization as a factor economic integration within EAEU - Yurova, N.V.; Perova, N.S. (KSU Publ., 2020)
this article is based on trend analysismodern digital development, as well as the prospects are consideredthe impact of the digitalization process and the introduction of new technologies oneffectiveness of Eurasian integration. It is shown thatcoordinated decision-making in the Eurasian Еconomic Union in terms of regulating new technological phenomena:ensure the competitive advantage of national economiesmember States and the Union as a whole.
Keywords: Digitalization; integration; EurasianЕconomic Union; digital technologies; globalization